The core microbiome of Carya illinoinensis (pecan) seedlings of different maternal pecan cultivars from the same orchard - Cervantes, Kimberly; Heerema, Richard J.; Randall, Jennifer J. (Frontiers in Microbiomes, 2022)
Carya illinoinensis (pecan) produce a high valued and desired nut crop; with production expanding worldwide. Important attributes of pecans and their ability to adapt to different environments aside from their native regions are currently being investigated. Microbial communities are known to play an important role in crop productivity and overall plant health. Studies in other plant species have shown that the plant microbiome may be influenced by both the environmental conditions and genetics of the plant. Microbiota research in pecan is in its early stages and here we report insights into the core microbiome of seedlings derived from five pecan cultivars located in an orchard from Las Cruces, New Mexico. Seeds from open-pollinated pecan cultivars (‘Burkett’, ‘Mandan’, ‘Pawnee’, ‘Western’, and ‘Wichita’) were collected and grown in a quarantine greenhouse under highly regulated conditions. DNA from the resulting seedlings were used for next generation sequencing (MiSeq) for 16S and ITS and microbiome analyses revealed significant differences in microbial composition and relative abundance (bacterial and fungal) between seedling organs, with roots having the highest alpha diversity followed by stems and leaves. Bacterial family Chitinophagaceae was identified to be most relatively abundant in the roots of seedlings compared to the bacterial families Rhizobiaceae and Moraxellaceae, which were found to be most relatively abundant in the stems and leaves, respectively. Analyses also indicated that there were several families (bacterial families: Rhizobiaceae, Enterobacteriaceae, Chitinophagaceae, Burkholderiaceae, Sphingomonadaceae, Pseudomonadaceae, Moraxellaceae, Microscillaceae, Rubritaleaceae, Caulobacteraceae; and fungal families: Serendipitaceae, Nectriaceae, Ophiostomataceae, Hypocreaceae, Aspergillaceae, and Cephalothecaceae) that were found in all seedlings and these constitute a core microbiome for pecan. There were also differences in microbial composition (bacterial and fungal) between seedlings from different maternal pecan cultivars and these differences are proposed to constitute a signature microbiome for the maternal cultivar. As pecan trees continues to extend to other growing regions it is important to understand the role that these microbes play in pecan. By establishing the core microbiome of pecans, the selection of microbes for breeding and improving pecan production will become a possibility.